2017
DOI: 10.1155/2017/3106871
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Oxygen Requirement beyond Prematurity: A Case of Acquired Pulmonary Vein Stenosis

Abstract: Acquired pulmonary vein stenosis is a rare cardiac defect and diagnosis can often be challenging, as many cases present with refractory or prolonged oxygen requirement over the expected course. Comorbid conditions can cloud this diagnosis further. Prognosis is poor for most patients. We present a case of idiopathic acquired pulmonary vein stenosis and discuss diagnostics, treatment options, and the need for further collaborative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A meta-analysis of infants with primary PVS reported that the majority of infants with PVS had left-to-right shunts [ 4 ], indicating elevated flow through the pulmonary veins, and higher shunt exposure time is associated with the development of PVS in infants with Down’s syndrome [ 5 ]. High flow may also be associated with anemia or infection, and PVS is known to be associated with necrotizing enterocolitis [ 6 ] and other conditions related to prematurity [ 7 , 8 ]. Abnormal pulmonary venous flow can also arise at discrete sites where a vein is compressed, folded, or otherwise partially obstructed, and cardiologists and surgeons at our institution have observed that the initial site of stenosis is often associated with these areas of disturbed blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of infants with primary PVS reported that the majority of infants with PVS had left-to-right shunts [ 4 ], indicating elevated flow through the pulmonary veins, and higher shunt exposure time is associated with the development of PVS in infants with Down’s syndrome [ 5 ]. High flow may also be associated with anemia or infection, and PVS is known to be associated with necrotizing enterocolitis [ 6 ] and other conditions related to prematurity [ 7 , 8 ]. Abnormal pulmonary venous flow can also arise at discrete sites where a vein is compressed, folded, or otherwise partially obstructed, and cardiologists and surgeons at our institution have observed that the initial site of stenosis is often associated with these areas of disturbed blood flow.…”
Section: Introductionmentioning
confidence: 99%